119 An Institutional Analysis of Venous Sinus Stenting and Cerebrospinal Fluid Shunting for Idiopathic Intracranial Hypertension. (April 2023) - Yamamoto, Erin A.; Mazur-Hart, David; Lee, Daniel; Schoettler Woll, S. Cody; Ramos, Christian Lopez; Munger, Daniel; Richie, Emma; Bozorgchami, Hormodz; Dogan, Aclan; Nesbit, Gary; Priest, Ryan; Falardeau, Julie; et al.
Abstract : INTRODUCTION: Idiopathic intracranial hypertension (IIH) is a debilitating disease that can present with severe vision loss. Although medical management is the first-line treatment, these cases commonly require intervention by either ventriculoperitoneal/pleural shunting (VPS) or, more recently, by venous sinus stenting (VSS). Unfortunately, this chronic disease can lead to multiple clinical encounters which increases financial burden. Therefore, identifying ways to effectively treat IIH definitively while limiting healthcare costs are of great interest. METHODS: This is a retrospective study of IIH patients diagnosed via modified Dandy criteria who received VPS (n=27) or VSS (n=27) from May 2008–May 2019. Visual outcomes were reported by a neuro-ophthalmologist at approximately 1-month post-procedure. Costs of emergency department as well as and outpatient/inpatient encounters for neurosurgery and ophthalmology were obtained from the index procedure to 3 years post-procedure. RESULTS: VSS patients had higher pre-intervention ophthalmology evaluation rates (stents: n = 22, 88.9%; shunts: n = 7, 23.1%; p < 0.0001). Papilledema was present in most patients (VSS 82.6% vs VPS 66.7%, p = 0.60) and all patients had stable/improved papilledema at follow-up. Two VSS patients (4.9%) required a second stent. Four VSS patients (9.8%) had a VPS placed. No VPS patients received a VSS. Encounter cost for VSS placement were more expensive than primary VPS placement (10, 749 vs 13, 648; p = 0.002). However, at 1.5 years after index procedure, cumulative VPS cost surpassed VSS and persisted at 3 years (22, 674 vs 17, 441, p = 0.039). CONCLUSIONS: VPS and VSS have similar visual outcomes with all cases having stable or improved papilledema. The upfront cost of VSS is greater than VPS; however, VPS quickly surpasses VSS in cost by 1.5 years after index procedure and continues to study endpoint at 3 years. These results may help guide multi-disciplinary care for patients with IIH.